Polymorphisms of MTHFR and MTR genes are not related to susceptibility to childhood ALL in north India - Nikbakht, M.; MalekZadeh, K.; Kumar Jha, A.; Askari, M.; Marwaha, R.K.; Kaul, D.; Kaur, J. (Experimental Oncology, 2012)
Background:Acute lymphoblastic leukemia (ALL) is the most worldwide common type of childhood cancer. Methylenetetrahydrofolate reductase (MTHFR) and 5-methyltetrahydrofolate-homocysteine methyltransferase (MTR) participate in folate pathways and are known as critical factors for DNA integrity as well as DNA hypomethylation. The aim of this work is to investigate frequency of MTHFR (677C→T and 1298A→C) and MTR (2756A→G) polymorphisms and their interaction with respect to possible effect on risk of childhood ALL among North Indian population. Procedure: A case control study from has been conducted on bone marrow and peripheral blood samples from 125 ALL patients and 100 sex-age matched healthy controls using PCR-RFLP method. Results: No statistically significant differences were observed for different genotypes between patients and controls (p>0.05). Significant difference for the risk of ALL in individuals having genotype of MTHFR 677TT (OR=0.61, 95% CI=0.21–1.77) and MTHFR 1298CC (OR=0.56, 95% CI=0.18–1.68) was not observed. The correlation of SNP of MTR gene and risk of ALL was not observed, too. Conclusions: The differences in distribution of possible combined genotypes of MTHFR (677C→T, 1298A→C) and MTR (2756A→G) between ALL patients and controls were statistically insignificant.